Evaluating the Impact of COVID-19 on a Regional Primary Percutaneous Coronary Intervention Service During the First Wave of COVID-19 - Adeogo Akinwale Olusan; Peadar Devlin (Interventional Cardiology: Reviews, Research, Resources)
Background: Primary percutaneous coronary intervention (pPCI) is the preferred reperfusion strategy in ST-segment elevation MI (STEMI). This study evaluates the impact of COVID-19 on the authors’ pPCI service. Methods: A retrospective study of referrals to the Belfast pPCI service between 23 March and 9 June 2020 – the period of the first full lockdown in the UK – was performed. All ECGs were reviewed alongside patient history. A pPCI turndown was deemed inappropriate if the review demonstrated that the criteria to qualify for pPCI had been met. The number of pPCIs was compared with 2019. Results: The unit had 388 referrals in 78 days, from which 134 patients were accepted for pPCI and 235 referrals were turned down. Of these, nine (4%) were deemed inappropriate. No referrals were turned down because of COVID-19. Of the nine inappropriate cases, six had pPCI following re-referral, two had routine PCI and one had takotsubo syndrome. From the accepted cohort, 85% had pPCI. In the appropriate turndown cohort, there was a final cardiovascular diagnosis in 53% (n=127) of patients, 1-year mortality was 16% (n=38), 55% (n=21) of which were due to a cardiovascular death. There was a 29% reduction in the number of pPCIs performed compared with 2019. Conclusion: During the first wave of COVID-19 there was a significant reduction in the number of pPCIs performed at the Department of Cardiology at Royal Victoria Hospital in Belfast. This was not due to an increase in referrals being inappropriately turned down. The majority of the cohort who had their referral turned down had a final cardiovascular diagnosis unrelated to STEMI; 1-year mortality in this group was significant.